Growth and Yield of Soybean on Various Types and Concentrations of Liquid Organic Fertilizer in Ultisols - Hesti Pujiwati; Nanik Setyowati; Desi Dwi Wahyuni; Zainal Muktamar (Journal of Applied Agricultural Science and Technology, 2021)
The application of a wed-based liquid organic fertilizer can increase the production of black soybeans (Glycine Max L. Merril). The study aimed to identify the best source and dose of liquid organic fertilizer (LOF) for black soybean growth and yield. The researchers used a three-times-repeated Completely Randomized Design (CRD) using a factorial layout. The first factor was the source of LOF, which included Siam weed (Chromolaena odorata, L.), Goat weed (Ageratum conyzoides L.), and yellow creeping daisy (Wedelia trilobata L.). The second factor was the concentration of weed-based LOF, consisted of water (control treatment); 12 ml/L; 16 ml/L; 20 ml/L. The results of the study show, weed-based LOF, namely LOF Yellow creeping daisy, Goat weed, and Siam weed, resulted in no significant difference in the growth and yield of the black soybean. Except for the variables of root fresh weight and number of pods per plant, the variation in concentration of weed-based liquid organic fertilizer had no significant effect on plant growth and yield.